2014
DOI: 10.1093/cid/ciu149
|View full text |Cite|
|
Sign up to set email alerts
|

The common occurrence of ceftriaxone-resistant methicillin sensitive Staphylococcus aureus at a community teaching hospital

Abstract: "Common Occurrence of Ceftriaxone-Resistant, Methicillin-Sensitive Staphylococcus aureus at a Community Teaching Hospital" by Aaron J. Pickering, Rahman Hariri, Lee H. Harrison, Jane W. Marsh, Amatullah Tasneem, Henry Freedy, Laura Wilson, and Hector Bonilla. [Clin Infect Dis. (2014), doi:10.1093/cid/ciu149]. Due to an honest error in the interpretation of a key lab test by the study microbiologist, with approval of all authors cited above, the authors are retracting this article from Clinical Infectious Disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These results are in line with previous data [47], which recorded that S. aureus was resistant to tetracycline and ampicillin. [48], who reported that 60% of S. aureus isolates were resistant to ceftriaxone. Multidrug-resistant S. aureus has been reported several times [49].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous data [47], which recorded that S. aureus was resistant to tetracycline and ampicillin. [48], who reported that 60% of S. aureus isolates were resistant to ceftriaxone. Multidrug-resistant S. aureus has been reported several times [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, uncertainties have remained around the efficacy of ceftriaxone against S. aureus . Although one study suggested high rates of resistance to ceftriaxone in methicillin-sensitive  S. aureus  (MSSA),22 it was subsequently retracted due to methodological flaws 23 24. A more recent study found 99% of MSSA isolates were ceftriaxone-susceptible 25.…”
Section: Discussionmentioning
confidence: 99%
“…The recent publication by Pickering et al [1] described a collection of methicillin-susceptible Staphylococcus aureus (MSSA) that displayed elevated ceftriaxone minimum inhibitory concentrations (MICs) when tested by Etest (bioMerieux, Durham, North Carolina) gradient diffusion and would have been called “Resistant” to ceftriaxone based on previous Clinical and Laboratory Standards Institute (CLSI) interpretive guidance. The authors reported that approximately 60% of MSSA tested at their institution would have been misclassified based on the current CLSI guidance, which recommends testing staphylococci only against penicillin and oxacillin or cefoxitin in order to infer susceptibility or resistance to other β-lactam agents.…”
Section: To the Editormentioning
confidence: 99%
“…We investigated the accuracy of the initial report by performing reference broth microdilution (BMD), disk diffusion, and Etest [both low (0.002–32 µg/mL) and high (0.016–256 µg/mL) range ceftriaxone Etest products] antimicrobial susceptibility testing on 8 pulsed field gel electrophoresis (PFGE)-matched pairs of MSSA from the Pickering study [1] reported to have mismatched ceftriaxone susceptibility. All 16 isolates were confirmed as oxacillin, cefoxitin, and ceftriaxone susceptible [2, 3] with BMD and disk methods.…”
Section: To the Editormentioning
confidence: 99%